PERAN PENTING PERATURAN PEMERINTAH (PP) RI NOMOR 46 TAHUN 2013 TERHADAP KEPATUHAN WAJIB PAJAK - sutono -; Bagus Kusuma Ardi (JURNAL EKONOMI MANAJEMEN AKUNTANSI, 2018)
AbstractTaxes have a very important role to play in the interests of the development process and finance government spending. The role of taxes is increasingly strategic especially when the economic conditions are weakening as it is today. Efforts to maximize tax revenues cannot rely solely on the role of the Director General of Taxes or tax officials, but the active role of taxpayers is also needed to be a very important factor in achieving tax revenue success. Therefore, one of the government's anticipations to continue maximizing the income / income from the taxation sector is through the issuance of Government Regulation (PP) of the Republic of Indonesia Number 46 of 2013 concerning 1% Final Tax for taxpayers with certain gross circulation or more commonly called PP Number 46 of 2013. PP No. 46 of 2013 has an important role in tax compliance. With this PP Number 46 of 2013, it is expected that taxpayers can comply with their obligations which include administration, calculation, deposit / payment, and reporting of income tax payable. Keywords: PP Number 46 of 2013, Taxpayer Compliance, Taxpayers AbstrakPajak memiliki peran yang sangat penting untuk kepentingan proses pembangunan dan membiayai pengeluaran pemerintah. Peran pajak semakin strategis terutama pada saat kondisi ekonomi yang melemah seperti saat ini. Usaha memaksimalkan penerimaan pajak tidak dapat hanya mengandalkan peran dari Dirjen Pajak maupun petugas pajak, tetapi dibutuhkan juga peran aktif dari para wajib pajak adalah menjadi faktor yang sangat penting dalam hal mencapai keberhasilan penerimaan pajak. Oleh sebab itu, salah satu antisipasi pemerintah untuk terus memaksimalkan pengupayaan pendapatan/penerimaan dari sektor perpajakan adalah melalui penerbitan Peraturan Pemerintah (PP) Republik Indonesia Nomor 46 Tahun 2013 tentang Pajak Final 1 % untuk wajib pajak dengan peredaran bruto tertentu atau lebih umum disebut PP Nomor 46 Tahun 2013. PP Nomor 46 Tahun 2013 memiliki peran penting terhadap kepatuhan wajib pajak. Dengan PP Nomor 46 Tahun 2013 ini, maka diharapkan wajib pajak dapat patuh terhadap kewajibannya yang meliputi administrasi, penghitungan, penyetoran/pembayaran, dan pelaporan pajak penghasilan yang terutang.  Kata kunci: PP Nomor 46 Tahun 2013, Kepatuhan Wajib Pajak, Wajib Pajak